The Normativity of Habermas’s Public Sphere from the Vantage Point of Its Evolution - Hułas, Maciej (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2019)
The paper argues that the original normativity that provides the basis for Habermas’s model of the public sphere remains untouched at its core, despite having undergone some corrective alterations since the time of its first unveiling in the 1960s. This normative core is derived from two individual claims, historically articulated in the eighteenth-century’s “golden age” of reason and liberty as both sacred and self-evident: (1) the individual right to an unrestrained disposal of one’s private property; and (2) the individual right to formulate one’s opinion in the course of public debate. Habermas perceives the public sphere anchored to these two fundamental freedoms/rights as an arena of interactive opinion exchange with the capacity to solidly and reliably generate sound reason and public rationality. Despite its historical and cultural attachments to the bourgeois culture as its classical setting, Habermas’s model of the public sphere, due to its universal normativity, maintains its unique character, even if it has been thoroughly reformulated by social theories that run contrary to his original vision of the lifeworld, organized and ruled by autonomous rational individuals.